The Effectiveness of Problem-Based Learning (PBL) and Guided Inquiry Models Assisted by Virtual Lab Media on Students' Critical Thinking Skills - Maryam, Siti; Munzil, Munzil; Suharti, Suharti (J-PEK (Jurnal Pembelajaran Kimia), 2023)
This research aims to determine the effectiveness of the PBL (Problem-Based Learning) model and guided inquiry assisted by virtual lab media in enhancing students' critical thinking skills on reaction rate material. The research design used was a Quasi-Experimental Pretest-Posttest Control Group Design. The experimental class used the PBL and guided inquiry models, while the control class was taught using conventional learning models. Both the experimental and control classes used virtual lab media (Crocodile Chemistry). The data analysis techniques used included descriptive analysis, hypothesis testing using one-way ANOVA to determine differences, and the N-Gain test to determine the effectiveness differences of each learning model used. The results showed significant differences in students' critical thinking skills between those who learned using the PBL model, guided inquiry, and conventional methods. The PBL and guided inquiry learning models assisted by virtual lab media were more effective in improving students' critical thinking skills compared to the conventional learning model assisted by virtual lab media. However, the PBL learning model was more effective than the guided inquiry model in enhancing students' critical thinking skills.